LEVEL OF PARENTAL KNOWLEDGE ABOUT PROVIDING A HEALTHY MP-ASI MENU IN EFFORTS TO PREVENT STUNTING IN TODDLERS (6-24 MONTHS) - Tinaweng, Novita Sania; Andriani, Sri; Haji Jafar, Cindy Puspita Sari (Universitas Negeri Gorontalo, 2025)
MP-ASI represents a critical transition period for toddlers (6-24 months) requiring precise nutritional fulfilment by parents to meet optimal growth and development needs. Children are at risk of experiencing growth and developmental disorders or stunting in the early stages of life when it is not well fulfilled. Thus, parental knowledge plays a crucial role in ensuring proper MP-ASI provision. The purpose of this study is to assess the parental knowledge level regarding providing healthy MP-ASI menus. This study is classified as a quantitative study with a descriptive design, employing a descriptive survey approach. The population consists of all mothers with toddlers (6-24 months) in the working area of Puskesmas Limboto, Gorontalo Regency, totalling 1,249 respondents selected using cluster sampling, with a sample of 302 respondents. The instrument used is the â€œQuestionnaire to asses parents' knowledge about infant complementary feeding.â€ Data analysis is conducted using univariate analysis. The findings indicate that the level of maternal knowledge regarding the provision of healthy MP-ASI menus is categorized as good for 176 respondents (58.3%), fair for 108 respondents (35.8%), and poor for 18 respondents(6.0%). In conclusion, some mothers with toddlers (6-24 months) possess good knowledge regarding providing healthy MP-ASI menus. Therefore, it is imperative for research institutions to continue prioritizing education efforts to raise public awareness regarding the importance of comprehensively providing appropriate MP-ASI through integrated maternal and child health services programs.